Marine super-hydrophobic anti-icing surface and preparation method thereof
By using ultrafast laser on the surface of titanium alloy, it is solved by inducing plasma precision processing to form a layered micro-nano structure and modifying fluoroalkyl low-surface tension compounds, the existing superhydrophobic anti-icing surfaces are insufficient adhesion and poor durability in marine applications, and the marine superhydrophobic anti-icing surface with excellent wear resistance and excellent anti-icing performance is achieved.
Patent Information
- Application Number
- CN202411723657.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-25
AI Technical Summary
The existing superhydrophobic anti-ice surfaces have problems such as weak adhesion, low durability, poor applicability and complex production processes in marine applications.
Ultrafast laser-induced plasma precision machining (LIPPM) process is used to perform non-contact liquid-immersion laser processing on the surface of the titanium alloy to form a layered micro-nano structure array surface, and chemically modify it using fluoroalkyl low-surface tension compound modifiers to prepare marine superhydrophobic anti-ice surface.
High contact angle and low rolling angle are achieved, which significantly improves the wear resistance of the surface and anti-ice effect, extends the delay time of icing, reduces the shear strength of ice, and simplifies the preparation process.
Smart Images

Figure CN119684901A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a marine super-hydrophobic anti-icing surface and a preparation method thereof, and belongs to the technical field of marine anti-icing engineering. Background Art
[0002] With the continuous expansion of marine activities such as marine transportation, deep-sea mining, and marine aquaculture, marine development is of great significance to economic development, and the demand for ships and marine engineering equipment is increasing rapidly. However, the surface of ships and marine engineering equipment operating in low-temperature areas such as the polar regions still faces severe frost and ice formation, so anti-icing of the surface of ships and marine engineering equipment is an engineering problem that needs to be solved urgently.
[0003] Titanium and its alloys are widely used in the field of ships and marine equipment, but the oxide film naturally formed on its surface cannot effectively prevent ice. In view of the current status of surface anti-icing technology research, constructing an anti-icing surface is an effective technical means. Among them, the super-hydrophobic surface reduces the contact between the liquid and the substrate surface due to its micro-nano structure and air chamber between the structures, maintains a stable Cassie-Baxter state, increases the surface freezing delay time, and reduces the surface ice shear strength, thereby achieving a certain degree of anti-icing effect, which has high research significance and application prospects.
[0004] Although there are currently a variety of super-hydrophobic and anti-icing surface preparation technologies, there are common problems such as weak adhesion between the super-hydrophobic coating and the substrate surface, low durability, poor applicability, and complex production process.
[0005] Therefore, there is an urgent need to develop a superhydrophobic anti-icing surface and its preparation method with good anti-icing effect, wide application scenarios and simple preparation process. Summary of the invention
[0006] The purpose of the present invention is to solve the problems in the prior art that the super-hydrophobic coating has weak adhesion to the substrate surface, low durability, poor applicability, and complicated manufacturing process.
[0007] In order to achieve the purpose of solving the above-mentioned problems, the technical solution adopted by the present invention is to provide a marine super-hydrophobic anti-icing surface and a preparation method thereof.
[0008] A first aspect of the present invention provides a method for preparing a marine super-hydrophobic anti-icing surface, comprising the following steps:
[0009] Step 1, pretreating the titanium alloy Ti6Al4V to obtain a substrate surface;
[0010] Step 2: Using ultrafast laser induced plasma precision machining (LIPPM) technology to perform non-contact immersion laser processing on the surface of the substrate in step 1 to obtain a hierarchical micro-nano structure array surface;
[0011] Step 3: 1 mL of fluoroalkyl low surface tension compound modifier (PFAS) is coated on the surface of the hierarchical micro-nanostructure array described in step 2 to directly obtain the marine super hydrophobic anti-icing surface. The modification temperature is set to 25°C.
[0012] Preferably, in step 1, the pretreatment method comprises: firstly finely polishing the titanium alloy Ti6Al4V for 5 minutes using a metallographic polisher, and then ultrasonically cleaning the titanium alloy Ti6Al4V for 20 minutes using anhydrous ethanol and deionized water respectively.
[0013] The beneficial effects of this technical solution are as follows: pretreatment before processing can remove the oxide layer and stains on the surface while ensuring a smooth surface; ultrasonic cleaning with anhydrous ethanol and deionized water can prevent interference from other substances; fine surface polishing helps reduce the adhesion of bubbles on the surface and the absorption of laser energy during processing, thereby ensuring processing quality.
[0014] Preferably, in the step 2, during the ultrafast laser-induced plasma precision processing, the ultrafast laser is a picosecond laser or a femtosecond ultrafast laser with a pulse width of ≤10ps, and the liquid medium used in the non-contact immersion laser processing is deionized water. During the processing, the deionized water is always 2.5mm above the substrate surface.
[0015] Preferably, in step 2, during the ultrafast laser-induced plasma precision machining process, the scanning frequency is 50 times, and the interval between scanning lines is 20 to 40 μm.
[0016] Preferably, in step 2, when ultrafast laser-induced plasma precision processing is performed on the substrate surface, a bubble blowing device is used to ensure that the rising bubbles are promptly moved away from the processing area to prevent the bubbles during processing from affecting the LIPPM process.
[0017] Preferably, in step 2, the surface of the hierarchical micro-nanostructure array has a regular micron-scale stacking structure and a uniform nano-scale stacking structure embedded therein, the array period is 20 to 40 μm, the overall depth of the array is 72 μm, the overall scale of the micron-scale stacking structure is 0.2 μm, and the overall scale of the nano-scale stacking structure is 41 nm.
[0018] The beneficial effects of this technical solution are as follows: the ultrafast laser used in step 2 is injected into the deionized water to induce high-energy plasma, thereby achieving thermal ablation and mechanical impact to remove the surface of the titanium alloy Ti6Al4V substrate; since plasma has different energy levels and levels, the hierarchical micro-nanostructure array surface is obtained; the deionized water is always 2.5 mm higher than the substrate surface to ensure that the size and magnitude of the generated bubbles are small, thereby improving the processing accuracy.
[0019] Since the laser energy is incident in a Gaussian mode, the energy gradually weakens from the center to the edge, resulting in a hierarchical energy distribution of the plasma. By adjusting the interval and scanning frequency of the scanning lines, hierarchical micro-nanostructure array surfaces of different scales can be obtained.
[0020] Preferably, in step 3, the fluoroalkyl low surface tension compound consists of methyl nonafluoroisobutyl ether, methyl nonafluorobutyl ether and a fluorine-containing lipid polymer.
[0021] The beneficial effect of this technical solution is that the hierarchical micro-nanostructure array surface provides effective support for hydrophobic non-polar carbon-fluorine-based substances, thereby improving the wear resistance of the surface.
[0022] The regular micrometer-scale stacking structure on the surface of the hierarchical micro-nanostructure array and the uniform nanoscale stacking structure embedded therein, combined with the air chamber between the structures, effectively reduce the contact area and contact time between the droplets and the substrate, as well as the mechanical connection between the substrate surface and the ice layer, and increase the stress notch on the substrate surface, thereby having a higher freezing delay time and smaller ice shear strength. The thermal insulation effect of the air chamber also slows down the freezing process of the supercooled droplets.
[0023] The second aspect of the present invention provides a marine super-hydrophobic anti-icing surface prepared by the above method.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. LIPPM combined with chemical modification was used to obtain a super-hydrophobic surface with a hierarchical micro-nano structure, with a contact angle of up to 164.411° and a rolling angle as low as 1.05°. The hierarchical micro-nano structure array surface provides effective support for hydrophobic non-polar carbon-fluorine-based substances, improving the wear resistance of the surface.
[0026] 2. The hierarchical micro-nanostructure array surface combined with the air chamber between the structures in the present invention effectively reduces the contact area and contact time between the droplets and the substrate, as well as the mechanical connection between the substrate surface and the ice layer, and increases the stress notch on the substrate surface. It has a higher freezing delay time and smaller ice shear strength. The heat insulation effect of the air chamber also slows down the freezing process of the supercooled droplets.
[0027] 3. The LIPPM in the present invention has a wide range of processing materials, and the surface of the hierarchical micro-nanostructure array can be quickly modified to obtain a super-hydrophobic and ice-resistant surface. The preparation process is simple and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the LIPPM processing principle diagram and the bubble blowing equipment used in the present invention:
[0029] Figure 21 is a microstructure diagram of the hierarchical micro-nanostructure array surface in Example 1 of the present invention, wherein (a) is a uniform array structure on the surface; and (b) is a regular micron-scale stacked structure and a uniform nano-scale stacked structure embedded therein.
[0030] Figure 3 (a) contact angle and (b) sliding angle of the super-hydrophobic surface of the hierarchical micro-nanostructure array in Example 1 of the present invention.
[0031] Figure 4 The figures are the situations where the droplets collide with different surfaces in Example 1 of the present invention and Comparative Examples 1-2, wherein (a) is the situation where the droplets collide with a horizontal surface, and (b) is the situation where the droplets collide with an inclined surface.
[0032] Figure 5 It is a test diagram of frosting and defrosting performance of Example 1 of the present invention and Comparative Examples 1-2;
[0033] Figure numerals: 1 - ultrafast laser; 2 - optical path module; 3 - focused light source; 4 - processing container; 5 - bubble blowing equipment; 6 - deionized water. DETAILED DESCRIPTION
[0034] In order to make the present invention more clearly understood, a preferred embodiment is described in detail with reference to the accompanying drawings as follows:
[0035] like Figure 1-5 As shown, the present invention provides a marine super-hydrophobic anti-icing surface and a preparation method thereof.
[0036] Example 1
[0037] S1. Preparation of sample substrate surface structure:
[0038] S11. Pre-treating the titanium alloy Ti6Al4V7 to obtain a substrate surface, wherein the pre-treatment comprises: firstly finely polishing the titanium alloy Ti6Al4V7 for 5 minutes using a metallographic polisher, and then ultrasonically cleaning the titanium alloy Ti6Al4V7 for 20 minutes using anhydrous ethanol and deionized water respectively;
[0039] S12. Figure 1 As shown, after the picosecond laser with a pulse width of 10ps is emitted from the ultrafast laser 1, a focused light source 3 is generated after passing through the optical path module 2, and the surface of the titanium alloy Ti6Al4V7 substrate placed in the processing container 4 and immersed in deionized water 6 is subjected to LIPPM processing. During the processing, the deionized water 6 is always 2.5mm higher than the surface of the titanium alloy Ti6Al4V7 substrate. The laser scanning frequency of the ultrafast laser 1 is controlled 50 times, and the interval of the scanning line is 30μm, so as to obtain a hierarchical micro-nano structure array surface; during the process, a bubble blowing device 5 is used to ensure that the rising bubbles are away from the processing area in time to prevent the bubbles in the processing from affecting the LIPPM process;
[0040] S2. Surface chemical modification: 1 mL of PFAS modifier is coated on the surface of the hierarchical micro-nanostructure array described in S12 to directly obtain a marine super-hydrophobic and anti-icing surface, and the modification temperature is set to 25°C; wherein the fluoroalkyl low surface tension compound PFAS is composed of methyl nonafluoroisobutyl ether, methyl nonafluorobutyl ether and fluorine-containing lipid polymers.
[0041] Embodiment 2: A design of a marine super-hydrophobic anti-icing surface and a preparation method thereof, comprising the following steps:
[0042] S1. Preparation of sample substrate surface structure:
[0043] S11. Pre-treating the titanium alloy Ti6Al4V7 to obtain a substrate surface, wherein the pre-treatment comprises: firstly finely polishing the titanium alloy Ti6Al4V7 for 5 minutes using a metallographic polisher, and then ultrasonically cleaning the titanium alloy Ti6Al4V7 for 20 minutes using anhydrous ethanol and deionized water respectively;
[0044] S12. Figure 1 As shown, after the picosecond laser with a pulse width of 10ps is emitted from the ultrafast laser 1, a focused light source 3 is generated after passing through the optical path module 2, and the surface of the titanium alloy Ti6Al4V7 substrate placed in the processing container 4 and immersed in deionized water 6 is subjected to LIPPM processing. During the processing, the deionized water 6 is always 2.5mm higher than the surface of the titanium alloy Ti6Al4V7 substrate. The laser scanning frequency of the ultrafast laser 1 is controlled 50 times, and the interval of the scanning line is 40μm, so as to obtain a hierarchical micro-nano structure array surface; during the process, a bubble blowing device 5 is used to ensure that the rising bubbles are away from the processing area in time to prevent the bubbles in the processing from affecting the LIPPM process;
[0045] S2. Surface chemical modification: 1 mL of PFAS modifier is coated on the surface of the hierarchical micro-nanostructure array described in S12 to directly obtain a marine super-hydrophobic and anti-icing surface, and the modification temperature is set to 25°C; wherein the fluoroalkyl low surface tension compound PFAS is composed of methyl nonafluoroisobutyl ether, methyl nonafluorobutyl ether and fluorine-containing lipid polymers.
[0046] Embodiment 3: A design of a marine super-hydrophobic anti-icing surface and a preparation method thereof, comprising the following steps:
[0047] S1. Preparation of sample substrate surface structure:
[0048] S11. Pre-treating the titanium alloy Ti6Al4V7 to obtain a substrate surface, wherein the pre-treatment comprises: firstly finely polishing the titanium alloy Ti6Al4V7 for 5 minutes using a metallographic polisher, and then ultrasonically cleaning the titanium alloy Ti6Al4V7 for 20 minutes using anhydrous ethanol and deionized water respectively;
[0049] S12. Figure 1 As shown, after the picosecond laser with a pulse width of 10ps is emitted from the ultrafast laser 1, a focused light source 3 is generated after passing through the optical path module 2, and the surface of the titanium alloy Ti6Al4V7 substrate placed in the processing container 4 and immersed in deionized water 6 is subjected to LIPPM processing. During the processing, the deionized water 6 is always 2.5mm higher than the surface of the titanium alloy Ti6Al4V7 substrate. The laser scanning frequency of the ultrafast laser 1 is controlled 50 times, and the interval of the scanning line is 20μm, so as to obtain a hierarchical micro-nano structure array surface; during the process, a bubble blowing device 5 is used to ensure that the rising bubbles are away from the processing area in time to prevent the bubbles in the processing from affecting the LIPPM process;
[0050] S2. Surface chemical modification: 1 mL of PFAS modifier is coated on the surface of the hierarchical micro-nanostructure array described in S12 to directly obtain a marine super-hydrophobic and anti-icing surface, and the modification temperature is set to 25°C; wherein the fluoroalkyl low surface tension compound PFAS is composed of methyl nonafluoroisobutyl ether, methyl nonafluorobutyl ether and fluorine-containing lipid polymers.
[0051] Comparative Example 1:
[0052] This comparative example provides a preparation method for a smooth substrate surface, and the preparation method specifically includes: firstly, finely polishing the titanium alloy Ti6Al4V7 for 5 minutes using a metallographic polisher, and then ultrasonically cleaning the titanium alloy Ti6Al4V7 for 20 minutes using anhydrous ethanol and deionized water respectively to obtain a smooth substrate surface.
[0053] Comparative Example 2:
[0054] This comparative example provides a preparation of a chemically modified smooth substrate surface, and the preparation method specifically includes: first, finely polishing the titanium alloy Ti6Al4V7 for 5 minutes using a metallographic polisher, and then ultrasonically cleaning with anhydrous ethanol and deionized water for 20 minutes respectively to obtain a smooth substrate surface. 1 mL of PFAS modifier is applied to the smooth substrate surface to directly obtain a chemically modified smooth substrate surface, and the modification temperature is set to 25°C; wherein the fluoroalkyl low surface tension compound PFAS is composed of methyl nonafluoroisobutyl ether, methyl nonafluorobutyl ether and a fluorinated lipid polymer.
[0055] 1. SEM detection:
[0056] The micro-nanostructure scale and morphology of the hierarchical micro-nanostructure array surface in Example 1 were observed by scanning electron microscopy (SEM). Figure 2 shown.
[0057] from Figure 2(a) shows that the surface has a uniform and ordered array structure. Figure 2 (b) It can be observed that there is a clear regularity of micron-scale stacking structure and the uniform nano-scale stacking structure embedded therein. This structure and the air chamber between the structures significantly reduce the contact area and contact time between the droplet and the substrate surface, improve the surface superhydrophobicity, delay the freezing time, and reduce the ice shear strength, which has great advantages in constructing marine superhydrophobic anti-icing surfaces.
[0058] 2. Detect hydrophobicity:
[0059] The contact angle and rolling angle of the surfaces prepared in the above-mentioned Example 1 and Comparative Examples 1-2 were measured using an SDC-200S contact angle analyzer. The experimental results are shown in Table 1. The contact angle and rolling angle of the super-hydrophobic surface of the hierarchical micro-nanostructure array in Example 1 are shown in Table 1. Figure 3 As shown. The hydrophobic comparison between Example 1 and Comparative Examples 1-2 shows that the hierarchical micro-nanostructure array surface prepared by the technical solution of the present invention has a higher contact angle and a lower rolling angle after chemical modification; the droplets are rebounded after hitting the surface of the embodiment with an inclination of 0° to 20° at the collision speed of 0.44m / s and 0.98m / s, as shown in FIG. Figure 4 As shown, the droplets in Comparative Examples 1 and 2 cannot completely bounce off the surface. In summary, the surface prepared by the technical solution of the present invention has a special hierarchical micro-nano structure and chemical modification, which can significantly reduce the contact area between the droplet and the substrate surface and has good superhydrophobic performance.
[0060] Table 1
[0061] Contact angle (°) Roll angle (°) Example 1 164.411 1.050 Comparative Example 1 87.138 12.650 Comparative Example 2 108.647 15.020
[0062] 3. Detect anti-icing performance:
[0063] The cooling circulation system was used to test the anti-icing performance of the surfaces prepared in the above-mentioned Example 1 and Comparative Examples 1-2, including ice delay time, ice shear strength, frosting and defrosting tests. Among them:
[0064] (1) The freezing delay time test specifically includes: observing the time of the entire freezing solidification stage of 4 μL deionized water on the -10°C substrate surface. The experimental results are shown in Table 2. By comparing Example 1 with Comparative Examples 1-2, it can be seen that the hierarchical micro-nanostructure array surface prepared by the technical solution of the present invention has a higher freezing delay time, which is much higher than Comparative Examples 1-2.
[0065] Table 2
[0066] Complete freezing cycle(s) Example 3072 Comparative Example 1 18 Comparative Example 2 972
[0067] (2) The ice shear strength test specifically includes: at -15°C, using a push-pull force meter to observe the maximum tangential force when a 26 μL deionized water ice column is pushed, and calculating the ice shear strength of the surface. The experimental results are shown in Table 3. By comparing Example 1 with Comparative Examples 1-2, it can be seen that the hierarchical micro-nanostructure array surface prepared by the technical solution of the present invention has a lower ice shear strength, which is much lower than Comparative Examples 1-2.
[0068] Table 3
[0069] Ice shear strength(kPa) Example 13 Comparative Example 1 382 Comparative Example 2 62
[0070] (3) Frosting and defrosting tests specifically include:
[0071] An industrial camera was used to record the frost formation process at -15°C and the defrosting process at 25°C, and the frost branches morphology and density were observed. Figure 5 As shown, compared with comparative examples 1 to 2, sparse and tall frost branches grow on the surface of the hierarchical micro-nanostructure array prepared by the technical solution of the present invention, and the surface droplets are aggregated and distributed after defrosting.
[0072] In summary, the surface prepared by the technical solution of the present invention has a special hierarchical micro-nano structure and chemical modification, which can significantly increase the freezing delay time, reduce the ice shear strength, inhibit the formation of frost branches, and has an excellent anti-icing effect.
[0073] 4. Detection of wear resistance:
[0074] The surface prepared in Example 1 was subjected to a friction test, and the contact angle and rolling angle of the surface after friction were measured, specifically comprising: 800# SiC sandpaper was used to rub the substrate surface and a load of 100g was applied, and each friction of 80mm was a cycle at a speed of 10mm / s, and the contact angle and rolling angle changes within 25 cycles were recorded. The experimental results are shown in Table 4. After 25 friction cycles, the contact angle dropped to 153.146°, and the rolling angle increased to 6.15°, indicating that the surface with a special hierarchical micro-nano structure and chemical modification prepared by the technical solution of the present invention can significantly improve the wear resistance of the surface.
[0075] Table 4
[0076] 100g friction cycle (times) 5 10 15 20 25 Contact angle (°) 161.491 158.393 155.182 155.054 153.146 Roll angle (°) 3.16 4.48 4.78 5.13 6.15
[0077] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and equivalent changes made by using the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a marine super-hydrophobic anti-icing surface, characterized in that: The following steps are involved: Step 1, pretreating the titanium alloy Ti6Al4V to obtain a substrate surface; Step 2: Using ultrafast laser induced plasma precision machining (LIPPM) technology to perform non-contact immersion laser processing on the surface of the substrate in step 1 to obtain a hierarchical micro-nano structure array surface; Step 3: 1 mL of fluoroalkyl low surface tension compound modifier (PFAS) is coated on the surface of the hierarchical micro-nanostructure array described in step 2 to directly obtain the marine super hydrophobic anti-icing surface. The modification temperature is set to 25°C.
2. The method for preparing the marine super hydrophobic anti-icing surface according to claim 1, characterized in that: In the step 1, the pretreatment method includes: firstly finely polishing the titanium alloy Ti6Al4V for 5 minutes using a metallographic polishing instrument, and then ultrasonically cleaning the titanium alloy Ti6Al4V for 20 minutes using anhydrous ethanol and deionized water respectively.
3. The method for preparing the marine super-hydrophobic anti-icing surface according to claim 1, characterized in that: In the step 2, during the ultrafast laser-induced plasma precision processing, the ultrafast laser is a picosecond laser or a femtosecond ultrafast laser with a pulse width of ≤10ps, and the liquid medium used in the non-contact immersion laser processing is deionized water. During the processing, the deionized water is always 2.5mm above the substrate surface.
4. The method for preparing the marine super-hydrophobic anti-icing surface according to claim 1, characterized in that: In the step 2, during the ultrafast laser-induced plasma precision processing, the scanning frequency is 50 times, and the interval between the scanning lines is 20 to 40 μm.
5. The method for preparing the marine super hydrophobic anti-icing surface according to claim 1, characterized in that: In the step 2, a bubble blowing device is used when the substrate surface is subjected to ultrafast laser-induced plasma precision processing.
6. The method for preparing the marine super hydrophobic anti-icing surface according to claim 1, characterized in that: In the step 2, the surface of the hierarchical micro-nanostructure array has a regular micron-scale stacking structure and a uniform nano-scale stacking structure embedded therein, the array period is 20 to 40 μm, the overall depth of the array is 72 μm, the overall scale of the micron-scale stacking structure is 0.2 μm, and the overall scale of the nano-scale stacking structure is 41 nm.
7. The method for preparing the marine super-hydrophobic anti-icing surface according to claim 1, characterized in that: In the step 3, the fluoroalkyl low surface tension compound modifier is composed of methyl nonafluoroisobutyl ether, methyl nonafluorobutyl ether and a fluorine-containing lipid polymer.
8. A marine super hydrophobic anti-icing surface obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for preparing super-hydrophobic bionic metal surface through ultrafast laser technology
CN108393588A
Super-hydrophobic anti-icing aviation aluminum alloy surface and production method
CN111846193A
Preparation method for high-adhesion super-hydrophobic surface based on laser chemical composite process
CN113275223A
Super-hydrophobic surface with high durability and low ice adhesion and preparation method thereof
CN114589081A
Iron-based amorphous alloy coating based on laser microtexture and having super-hydrophobicity and corrosion resistance and preparation method of iron-based amorphous alloy coating
CN116814908A